A Missense Variant in Granulysin is Associated with the Efficacy of Pegylated-Interferon-Alpha Therapy in Chinese Patients with HBeAg-Positive Chronic Hepatitis B - Li J (Dove Medical Press, 2021)
Jing Li,1,* Haitao Chen,1,2,* Jiaxuan Chen,1,* Bin Zhou,1 Jinlin Hou,1 De-Ke Jiang1 1State Key Laboratory of Organ Failure Research, Guangdong Key Laboratory of Viral Hepatitis Research, Guangdong Institute of Liver Diseases, Department of Infectious Diseases and Hepatology Unit, Nanfang Hospital, Southern Medical University, Guangzhou, People’s Republic of China; 2School of Public Health (Shenzhen), Sun Yat-sen University, Shenzhen, People’s Republic of China*These authors contributed equally to this workCorrespondence: De-Ke Jiang; Jinlin HouState Key Laboratory of Organ Failure Research, Guangdong Key Laboratory of Viral Hepatitis Research, Guangdong Institute of Liver Diseases, Department of Infectious Diseases and Hepatology Unit, Nanfang Hospital, Southern Medical University, Guangzhou, People’s Republic of ChinaTel +86-20-62786533; +86-20-61641941Email dekejiang17@smu.edu.cn; jlhousmu@163.comPurpose: Granulysin (GNLY) is a cytotoxic granule that has been reported to have various antimicrobial activities. We evaluated the association between a missense variant in GNLY (rs11127) and treatment efficacy of pegylated interferon-alpha (PegIFNα) or nucleos(t)ide analogs (NUCs) in patients with chronic hepatitis B (CHB).Patients and Methods: We included a total of 1823 patients with hepatitis B e antigen (HBeAg)-positive CHB (954 patients treated with PegIFNα and 869 patients treated with NUCs) in four Phase IV multicenter randomized controlled trials. The association of the GNLY rs11127 genotype with the combined response (CR), defined as HBeAg seroconversion and hepatitis B virus (HBV) DNA level < 2000 IU/mL was evaluated. A polygenic score (PGS) was constructed to evaluate the cumulative effect of multiple single-nucleotide polymorphisms (SNPs), including rs11127 and several other SNPs, STAT4 rs7574865, CFB rs12614, and CD55 rs28371597, which were reported to be associated with CR.Results: GNLY rs11127 was significantly associated with CR in patients treated with PegIFNα. The CR rate in patients with the rs11127 CC genotype was higher than that with the CT or TT genotype (40.98% vs 30.34% or 27.09%, P = 0.003). Furthermore, a PGS integrating GNLY rs11127 and three other SNPs was significantly associated with CR in PegIFNα-treated patients (P < 0.001). However, no significant correlation was found between GNLY rs11127 and CR in NUCs-treated patients.Conclusion: GNLY rs11127 is an independent biomarker for predicting the response to PegIFNα therapy in HBeAg-positive CHB patients. Furthermore, the PGS, including GNLY rs11127, provides new insights for individualized treatment in clinical practice.Keywords: GNLY, rs11127, chronic hepatitis B, PegIFNα treatment, polygenic score